Āftāb-i Ajmer, kāmil : savāniḥ ʻumarī Ḥa̤zrat Ḵẖvājah Gẖarīb Navāz . - Cishtī, Malik Bashīr Aḥmad (Nāz Pablishing Hāʼūs, 1970)
On the life of the Indian Muslim saint of Ajmer, Muʻīnuddin Cishtī, 1143?-1234?